Modelagem e otimização de projeto de unidades de desidratação de gás natural por adsorção - Braun, Felipe Eduardo (2018)
The flexible polyhedron optimization method was used in the design of natural gas dehydration units by TSA (Temperature Swing Adsorption) adsorption in solid bed. The proposed optimization has comprised two approaches, the first based on empirical design rules established by practice over the years and synthesized in ’Gas Conditioning and Processing’ by CAMPBELL (2004). This methodology, focused on conceptual designs, was adapted to optimization, resulting in inequality equations or constraints. The results from this first approach were used as input for a second one, more accurate, based on phenomenological simulation. Part of the constraints used in the first approach was replaced by differential equations that represent mass balance, energy, adsorbent capture rate, etc. The objective of this work was to propose the lowest cost design of a unit present in an oil platform. With this purpose, an objective function was proposed based on CAPEX and OPEX. The optimization problem was implemented in Matlab software, applying the finite difference method to discretize the spatial domain of the partial differential equations. The comparative analysis between the two approaches pointed to significant savings and gain in accuracy when carrying out the project through the use of phenomenological modeling and optimization.